Sameness of plot in indirect translation. What events remain in complex translation chains? - Hongisto Tuuli; Taivalkoski-Shilov Kristiina (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
This paper deals with a central aspect related to translation that has been given surprisingly little attention in Translation Studies: sameness. We study sameness in a type of translation that according to previous studies entails additional shifts and losses - indirect translation. By indirect translation we mean a 'translation based on a text (or texts) other than (only) the ultimate source text' Our aim is to identify what stays the same in indirect literary translation in terms of plot. Our article is based on two case studies that comprehend particularly fuzzy chains of texts: the first Finnish translations of Robinson Crusoe and Peter Pan. Our main units of analysis are the plots of both works. We approach plot from a structural perspective and utilize plot function theory in our analysis. Our main research questions are: What in the plots of the two works studied has remained unaltered throughout the textual chain? What is the relation between plot elements that have been altered versus plot elements that have remained the same?